Web 2.0-Based E-Learning
DOI: 10.4018/978-1-60566-294-7.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Personal Knowledge Management Skills in Web 2.0-Based Learning

Abstract: At present, many Web 2.0 activities are being integrated into the e-learning spaces designed for learners. We need to analyze and learn from these activities to derive insights about their effectiveness, in order to promote the systematic application of technology in post-compulsory educational contexts, from undergraduate to postgraduate levels and also in professional training. This chapter deals with one aspect of “E-learning 2.0” (Downes, 2005) practices, specifically the importance of acquiring and master… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Ainsi, tous les étudiants ne possèdent pas les compétences nécessaires à une gestion optimale de leur EPA (Dabbagh et Kitsantas, 2012). Sur un plan plus technique, vu leur manque de connaissances des outils à disposition (Poellhuber, 2013), les apprenants nécessitent aide et intervention pédagogiques afin de choisir les outils adéquats en vue d'atteindre leurs objectifs d'apprentissage (Cigognini et al, 2011). De même, les résultats de ces recherches ne pourront pas être ignorés par les professeurs de l'enseignement supérieur ou les formateurs d'enseignants.…”
Section: Resultsunclassified
“…Ainsi, tous les étudiants ne possèdent pas les compétences nécessaires à une gestion optimale de leur EPA (Dabbagh et Kitsantas, 2012). Sur un plan plus technique, vu leur manque de connaissances des outils à disposition (Poellhuber, 2013), les apprenants nécessitent aide et intervention pédagogiques afin de choisir les outils adéquats en vue d'atteindre leurs objectifs d'apprentissage (Cigognini et al, 2011). De même, les résultats de ces recherches ne pourront pas être ignorés par les professeurs de l'enseignement supérieur ou les formateurs d'enseignants.…”
Section: Resultsunclassified
“…Most items were suggested in work by Van Braak (2004), but have been expanded with some items referring to the use of social networking sites (SNSs). An attempt to empirically find in our data the same categories (based on qualitative research), described by Cigognini, Pettenati and Edirisingha (2011) for the analysis of Web 2.0, was not successful. Some items did not find a place in these categories, and some others were linked with other categories than was suggested by these researchers.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Nowadays Web 2.0 offers a lot of support for this process. Cigognini, Pettenati, and Edirisingha (2011) contend that university students are not well prepared to use Web 2.0 technologies and applaud teaching of PKM skills to university students. Based on qualitative research they developed a system to analyze the PKM basic skills and high-er-order PKM skills.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research on PLEs has shown that social media can facilitate the creation of PLEs that help learners aggregate and share the results of learning achievements, participate in collective knowledge generation, and manage their own meaning making (Dabbagh & Kitsantas, 2012). However, despite these powerful learning affordances, students need support, guidance and pedagogical interventions to help them make the best possible use of social media to support their learning goals and achieve academic success (Cigognini, Pettenati, & Edirisingha, 2011;Clark, Logan, Luckin, Mee & Oliver, 2008).…”
Section: Personal Learning Environments or Ples Are A 21mentioning
confidence: 99%